2017
DOI: 10.1016/j.jval.2016.09.2398
|View full text |Cite
|
Sign up to set email alerts
|

Health State Preference Weights for the Glasgow Outcome Scale Following Traumatic Brain Injury: A Systematic Review and Mapping Study

Abstract: BackgroundValid and relevant estimates of health state preference weights (HSPWs) for Glasgow Outcome Scale (GOS) categories are a key input of economic models evaluating treatments for traumatic brain injury (TBI).ObjectivesTo characterize existing HSPW estimates, and model the EuroQol five-dimensional questionnaire (EQ-5D) from the GOS, to inform parameterization of future economic models.MethodsA systematic review of HSPWs for GOS categories following TBI was conducted using a highly sensitive search strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…The first is an ALDVMM implemented using the publicly available Stata command “aldvmm” [18] . This model has previously been applied for mapping across a range of clinical areas, including rheumatoid arthritis [18] , [19] , osteoarthritis [27] , ankylosing spondylitis [28] , and traumatic brain injury [29] . It has been shown to outperform other methods (linear regression, Tobit, and response mapping).…”
Section: Methodsmentioning
confidence: 99%
“…The first is an ALDVMM implemented using the publicly available Stata command “aldvmm” [18] . This model has previously been applied for mapping across a range of clinical areas, including rheumatoid arthritis [18] , [19] , osteoarthritis [27] , ankylosing spondylitis [28] , and traumatic brain injury [29] . It has been shown to outperform other methods (linear regression, Tobit, and response mapping).…”
Section: Methodsmentioning
confidence: 99%
“…Independent variables can influence component membership and/or each of the components in the mixture model part. This model has been used with success in previous mapping studies [4], [6], [7], [10], [11], [12].…”
Section: Methodsmentioning
confidence: 99%
“…It also impacts on the economy due to healthcare expenditure and productivity loss. 2 Around 8% of all TBIs are classified as severe (Glasgow Coma Scale (GCS) score of [3][4][5][6][7][8], which are more likely to result in death or long-lasting disability, compared with mild (GCS of [13][14][15] or moderate (GCS 9-12) head injury, for which the risk of death is lower, but still considerable. 1 3 Tranexamic acid reduces bleeding by inhibiting the breakdown of blood clots.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…A systematic review and EQ-5D utility mapping study was identified, which reported utility values for patients with TBI, based on their level of disability, as defined by the Glasgow Outcome Scale (GOS). 15 In the absence of GOS outcomes in the CRASH-3 trial, we used the DRS scores of CRASH-3 trial patients to estimate the proportion of patients in each GOS category, using a qualitative estimation involving a clinical expert. This resulted in an estimated 3094 patients with a good recovery, 1288 with moderate disability, 677 with severe disability and 124 in a vegetative state.…”
Section: Utilitymentioning
confidence: 99%